Comparative Study of BAX/BcL2 Expression Ratio in Menstrual Blood between Endometriosis Women and Women without Endometriosis - Arghya Wicaksana; Pande Made Dwijayasa; Rahajeng Rahajeng; Cholid Rohman Riskianto (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Endometriosis is characterized by the presence of endometrial tissue outside the uterus and is commonly associated with chronic pelvic pain and infertility. One of the endometrial changes that appear in the eutopic and ectopic endometrium of women with endometriosis is the regulation of apoptosis. The proportion value of the BAX/BcL-2 ratio is a crucial factor in determining the ability of cells to stimulate apoptosis. Higher apoptotic activity is linked to an increased BAX/BcL-2 ratio. The aim of this study was to compare the BAX/BcL-2 ratios in menstrual blood of endometriosis and non-endometriosis patients. Material and Methods: This research is a quantitative observational study with a cross-sectional method at dr. Saiful Anwar Malang. The case group was postoperative women with ovarian cysts with anatomical pathology examination results indicating endometriosis. While the control group was patients without endometriosis. Data analysis was carried out by using the Independent T Test with SPSS for Windows 19.0 software. Results: Each group consisted of 17 patients. The normality test for each variable shows p> 0.05. BAX average in patients with endometriosis 4556.29 ± 2338.33 and 6488.06 ± 2649.08 in patients without endometriosis (p = 0.031). The average BcL-2 in endometriosis patients was 6483.82±2489.36 and 4877.18±2023.82 in patients without endometriosis (p=0.047). The average BAX/BcL-2 ratio in patients with endometriosis was 0.698±0.19 and 1.367±0.26 in patients without endometriosis (p=0.000). Conclusion: The BAX/BcL-2 ratio in women with endometriosis cysts has a lower average rate than women without endometriosis cysts.